Archivo histórico de Caja Madrid: Fuentes monetarias y contables del Monte de Piedad de Madrid - Muñoz Serrulla, María Teresa (Revista General de Información y Documentación, 2007)
The documentary files from the Historical Archive of Caja Madrid are actually almost still unknown and non well studied. This article describes part of these files, specifically those related with monetary documentation and therefore opens new possibilities for investigation and studies in Numismatics.